KOMITMEN KEPEMIMPINAN DALAM MEMBANGUN BUDAYA KERJA ORGANISASI PENDIDIKAN - Herman, Herman (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2025)
Leadership commitment in building a positive and productive work culture can improve the quality of performance of educational organizations. This study aims to describe and analyze leadership commitment in building the work culture of educational organizations. This research uses a qualitative approach with a library research study method by conducting a literature review in analyzing data and information about leadership commitment in building the work culture of educational organizations. The results of this study indicate that leadership commitment in building the work culture of educational organizations, including: 1) commitment to the vision and mission of the organization by developing the vision and mission, communicating the vision and mission to all members of the organization, integrating the vision and mission into all aspects of organizational activities and evaluating and updating the vision and mission regularly, 2) commitment to building a solid work team by carrying out activities that increase the job satisfaction of team members and activities that support and improve the quality of work results, 3) commitment to work innovation by carrying out activities to develop and implement new and creative ideas, as well as activities to implement processes and use new technology and provide opportunities for team members to implement new and creative ideas, and 4) commitment to improvement and change. and 4) commitment to continuous improvement and change by implementing continuous improvement and change activities by work team members, and activities that can increase job satisfaction of education organization team members